SYARAT PERLU SUATU OPERATOR LINEAR A SEBAGAI GENERATOR DARI FUNGSI KOSINUS COS - Tri Widjajanti Widjajanti (Jurnal Natural, 2007)
This paper will discussed a linear operator A as generator of cosine function Cos by determining the necessary conditions for operator A as a generator of cosine function Cos.